Seeing the world as an African language speaker - Dowling, Tessa (University of Cape Town, 2014)
This lecture will be of interest to anyone who wishes to know more about the relationship between language and culture. Go to Seeing the world as an African language speaker Is the way we see the world influenced by our language, or is it the other way around: is our language influenced by the way we see the world? You’ve all heard (the rather faulty) example of the Inuit having many words for snow – and maybe even have heard of the South American language called Yagan with a word Mamihlapinatapei which refers to the desirous look two people give each other when they want to start something but are too hesitant to do so (what a wistful, romantic culture, you might think!) But what about here in South Africa? What is it about African languages that makes them uniquely different and astonishingly original in the way they are put together? This lecture will introduce you to some of the key features (both structural and metaphorical) of our languages, features essential to understanding their cultures.